Momentum in Tournaments: Evidence from Three-Cushion Billiards - Collins, Clay; Yoon, Jaeho (Advances in Social Sciences Research Journal, 2025)
This paper examines the effect of momentum on a sport without set limits, specifically, three-cushion billiards tournaments. Using Poisson estimation of inning-by-inning scores for the 2019 Union Mondiale de Billard (UMB) three-cushion billiards season, we determine the effects of player momentum and the mandatory mid-game break on scoring. We find no evidence of positive momentum, but instead find that “losing” the previous inning makes a player approximately 8.8% less likely to score in the following inning. We also find that the mid-game break does little to restore momentum to the losing player, but significantly helps the leading player.